2018
DOI: 10.1371/journal.pone.0196019
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-spontaneous nystagmus in patients with geotropic direction-changing positional nystagmus

Abstract: BackgroundPseudo-spontaneous nystagmus has been reported in patients with direction-changing positional nystagmus (DCPN). Recently, the concept of a “light cupula” has been introduced as a pathophysiology that can exhibit persistent geotropic DCPN. Patients with persistent DCPN could have different characteristics of nystagmus. Therefore, we investigated the pseudo-spontaneous nystagmus in patients with transient (canalolithiasis) and persistent (belong to light cupula theory) geotropic DCPN.MethodsIn this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Kim et al 40 reported that PSN was present in 100% of patients with a light cupula, while another study did not find PSN in some patients with a light cupula when they were sitting with the head upright. Hong et al 41 observed PSN more often in patients with pG-DCPN than in patients with transient DCPN, and the direction of PSN was toward the unaffected side. When the head is erect, an angle of 30° between the lateral semicircular canal and horizontal plane can place the ampulla in a higher position than the other semicircular canals, which causes the light cupula to deviate toward the utricle, leading to PSN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kim et al 40 reported that PSN was present in 100% of patients with a light cupula, while another study did not find PSN in some patients with a light cupula when they were sitting with the head upright. Hong et al 41 observed PSN more often in patients with pG-DCPN than in patients with transient DCPN, and the direction of PSN was toward the unaffected side. When the head is erect, an angle of 30° between the lateral semicircular canal and horizontal plane can place the ampulla in a higher position than the other semicircular canals, which causes the light cupula to deviate toward the utricle, leading to PSN.…”
Section: Discussionmentioning
confidence: 97%
“…Previous morphological studies of squirrel monkeys and computed tomography of human inner ear revealed that the top of the cupula of the HC faces outward, and it is speculated that the cupula of the HC is at an angle of approximately 20° to the median sagittal plane. 41 Turning the patient's head toward the affected side at a certain angle will result in the long axis of the affected cupula being parallel to the axis of gravity, which does not cause deflection of the cupula, and produces no nystagmus; this is when the null plane is observed, and the side of the null plane is consistent with the affected side. 14 In our study, 88.6% of the patients with pAG-DCPN and 93.3% of the patients with pG-DCPN had the second NP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the clinical data and resolution time differed between persistent and transient geotropic DCPN and suggested the mechanisms differed [6,8,12]. In one study, the conventional repositioning maneuver used to treat geotropic DCPN (HSCC-BPPV) was ineffective for patients with persistent geotropic DCPN [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported the occurrence of spontaneous nystagmus in the sitting position in patients with BPPV [7][8][9][10]. Such nystagmus is direction changing in nature, modulated by head position in the pitch plane.…”
Section: Introductionmentioning
confidence: 99%